Pengaruh Deposit Structure Dan Ownership Concentration Terhadap Pengungkapan Islamic Corporate Governance Pada Bank Syariah Di Indonesia Dan Malaysia - Hasna Katsurayya; Tettet Fitrijanti; Fury Khristianty Fitriyah (LPPM ISNJ Bengkalis, 2020)
This research aims to determine the effect of Deposit Structure and Ownership Structure on the disclosure of Islamic Corporate Governance (ICG). Deposit Structure is proxied by the percentage of the Profit Sharing Investment Account (PSIA) to assets, while Ownership Structure used in this research is Blockholder Ownership and Managerial Ownership. The research uses descriptive and verification method with quantitative analysis approach. The results show that simultaneous Profit Sharing Investment Account, Blockholder Ownership, and Managerial Ownership has significant effect on the disclosure of ICG. Partially, Profit Sharing Investment Account indicates significant positive effect on the disclosure of ICG, Blockholder Ownership shows significant positive effect on the disclosure of ICG, while the Managerial Ownership does not affect the disclosure of ICG.